Glucose metabolism in gestational diabetes and their relationship with fat mass / muscle mass index - Martínez Martínez María de los Angeles; Camarillo Romero Eneida del Socorro; Mendieta Zerón Hugo; Garduño García José de Jesús (Elsevier, 2024)
Introduction: During pregnancy, women experience metabolic changes that may induce insulin resistance, which can be traced to the blood glucose levels A number of factors may intervene in the metabolism of glucose in pregnant women; one of them is body composition. This factor is useful for studying metabolic diseases, for which the identification of the fat mass/muscle mass index (FMMMI) considered an especially relevant factor. Owing to their nature, techniques such as bioimpedance have been sparsely used for analysis during pregnancy. Aim: This study aimed to identify the relationship between fat mass / muscle mass index and glucose metabolism in pregnant women. Methods: This descriptive cross-sectional study included 231 women between the ages of 18 and 35 years and 24-28 weeks of gestation, who attended a state hospital for regular check-ups and exhibited risk factors for the development of gestational diabetes (GD) according to the Current Practice Guidelines in Primary Care. The participants underwent a physical examination, anthropometric measurements bio impedance were obtained, and oral glucose tolerance curves were constructed. FMMMI was calculated. Results: The prevalence of gestational diabetes was observed to be 13.4%. Women with a GD diagnosis had a significantly higher FMMMI than in those with no GD (0.746 ± 0.168 vs 0.567 ± 0.167;p < 0.005). The assessment of the FMMMI tertiles revealed that GD prevalence was higher in tertile 3 than in tertiles 1 and 2 (tertile 1: 2.6%; tertile 2: 9.1%; tertile 3: 24%). Conclusion: FMMMI is associated with glucose tolerance test response in pregnant women and a higher prevalence of GD.